Carnitine supplementation alleviates lipid metabolism derangements and protects against oxidative stress in non-obese hereditary hypertriglyceridemic rats - Cahova, Monika; Chrastina, Petr; Hansikova, Hana; Drahota, Zdenek; Trnovska, Jaroslava; Skop, Vojtech; Spacilova, Jana; Malinska, Hana; Oliyarnyk, Olena; Papackova, Zuzana; Palenickova, Eliska; Kazdova, Ludmila (Applied physiology, nutrition, and metabolism, 2015)
The aim of this study was to estimate the effect of carnitine supplementation on lipid disorders and peripheral tissue insulin sensitivity in a non-obese animal model of insulin resistance, the hereditary hypertriglyceridemic (HHTg) rat. Male HHTg rats were fed a standard diet, and half of them received daily doses of carnitine (500 mg·kg(-1) body weight) for 8 weeks. Rats of the original Wistar strain were used for comparison. HHTg rats exhibited increased urinary excretion of free carnitine and reduced carnitine content in the liver and blood. Carnitine supplementation compensated for this shortage and promoted urinary excretion of acetylcarnitine without any signs of (acyl)carnitine accumulation in skeletal muscle. Compared with their untreated littermates, carnitine-treated HHTg rats exhibited lower weight gain, reduced liver steatosis, lower fasting triglyceridemia, and greater reduction of serum free fatty acid content after glucose load. Carnitine treatment was associated with increased mitochondrial biogenesis and oxidative capacity for fatty acids, amelioration of oxidative stress, and restored substrate switching in the liver. In skeletal muscle (diaphragm), carnitine supplementation was associated with significantly higher palmitate oxidation and a more favorable complete to incomplete oxidation products ratio. Carnitine supplementation further enhanced insulin sensitivity ex vivo. No effects on whole-body glucose tolerance were observed. Our data suggest that some metabolic syndrome-related disorders, particularly fatty acid oxidation, steatosis, and oxidative stress in the liver, could be attenuated by carnitine supplementation. The effect of carnitine could be explained, at least partly, by enhanced substrate oxidation and increased fatty acid transport from tissues in the form of short-chain acylcarnitines.
Keywords: homeostáza; Gene Expression Regulation; mitochondriální DNA; oxidační stres; DNA, Mitochondrial; Insulin Resistance; antioxydant; Male; inzulinová rezistence; Genetic Predisposition to Disease; stéatose hépatique; syndrome métabolique; hypertriglyceridemie; Homeostasis; Kidney; Muscle, Skeletal; Hypertriglyceridemia; mass spectrometry; mužské pohlaví; metabolismus lipidů; potravní doplňky; insulin resistance; Carnitine; Dietary Supplements; spectrométrie de masse; kosterní svaly; krysa rodu Rattus; Animals; játra; karnitin; ledviny; zvířata; regulace genové exprese; Lipid Metabolism; Rats; antioxidant; Liver; Oxidative Stress; metabolic syndrome; genetická predispozice k nemoci; liver steatosis; insulinorésistance